Analysis of Islamic Religious Education Materials at Padjadjaran University: Characteristics, Learning Outcomes, and PPT Utilization - Muhammad Hizba Aulia; Saepul Anwar; Nandang Nursaleh (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study investigates the structure and relevance of Islamic Religious Education (PAI) teaching materials at Padjadjaran University, focusing on their impact on student learning outcomes and the effectiveness of instructional media. A qualitative approach was employed, utilizing thematic and content analysis. Data were gathered through interviews with lecturers, classroom observations, and an in-depth review of Semester Learning Plans (RPS) and PowerPoint (PPT) teaching materials. The analysis shows that current PAI materials successfully incorporate key themes such as Islamic moderation and anti-corruption values. However, they fall short in fostering active student engagement and interactivity. The use of static media, such as text-heavy PPTs, limits the development of critical thinking and practical application. To address these issues, the study recommends enhancing teaching materials with multimedia content and real-world case studies. Furthermore, aligning the curriculum with Outcome-Based Education (OBE) principles could strengthen the development of global competencies and 21st-century skills within an Islamic ethical framework. Improving PAI teaching materials through multimedia integration and OBE alignment can significantly enhance student engagement and learning outcomes. These strategies offer practical pathways to better prepare students to navigate contemporary challenges while upholding Islamic values.